Tolerance as a communicative category: Linguistic and linguodidactic aspect - Sobirzhonova Madina Ravshanbek kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article is of interest for research in the field of linguoculturology and intercultural communication. It is devoted to the differentiation of related concepts, "Tolerance". To this end, the author uses the method of comparing concepts. The hypothesis of the article is that the author considers these concepts to be independent, incoherent, and the keywords representing them, according to this hypothesis, are not synonyms. All three concepts seem to be extremely important for intercultural communication, but in Russian linguoculture they have different contents. Based on the research of concepts conducted on the material of the Russian language, the author compares these concepts and comes to the conclusion about the differences both in their linguistic representation and the representation of linguistic units in various types of discourse, and about the sign of connotation inherent in these linguistic units.